Semis direct dans la vallée moyenne de l'Ebre : Résumé des résultats et analyse économique - Arnal Atarés P. (Troisièmes rencontres méditerranéennes du semis direct, 2006)
Results from tillage trials in the mid Ebro valley are compared and an economic analysis is presented for the different techniques according to the results obtained.
3. Mediterranean Meeting on no Tillage, 2006/03/23-25, Zaragoza (Spain)